Data for "Influence of Arctic microlayers and algal cultures on sea spray hygroscopicity and the possible implications for mixed-phase clouds" - Merete Bilde; Sigurd Christiansen (Zenodo, 2020)
Dataset and data analysis for the paper on "Influence of Arctic microlayers and algal cultures on sea spray hygroscopicity and the possible implications for mixed-phase clouds" published in Journal of Geophysical Research: Atmospheres. The folder "CCN data analysis" contains the measured raw and processed CCN data, data analysis and presentation of the data (Figure 2-4). The fold "Modelling" gives the post-processed model output used for producingfigures 5-10.